The impact of devolution on local health expenditures anecdotes and some estimates from the Philippines - Capuno, Joseph J.; Solon, Orville Jose C. (The Philippine Review of Business and Economics, 1996)
The Local Government Code of 1991 stipulates (1) the devolution of health facilities, functions and personnel from the national government to local government units, and (2) a corresponding increase in central transfers to local government units. However, inter jurisdictional spillovers of local health programs and the locational bias of hospitals maintained by the national government are also the necessary consequences of decentralization. This paper presents estimates of the effects of devolved facilities, central transfers, cross-border use of facilities and the presence of retained hospitals on local health expenditure. Results show that (1) local health expenditures are positively affected by the number of devolved facilities in a given locality, (2) municipalities and cities are more responsive to block grants than provinces, and (3) poor facilities or those which absorbed inordinate number of health facilities tend to free ride on their richer neighbours.